The effect of snorkel breathing during front crawl swimming on respiratory muscle fatigue - Iggleden, C.; Lomax, M.; Fricker, R.; Jones, O.; Moffatt, S.; Poole, R. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The use of snorkels has become a popular training aid for competitive swimmers. However, the narrowed external airflow path associated with snorkel breathing (SB) presents an inspiratory and expiratory flow limitation, which has the potential to induce respiratory muscle fatigue (Rohrbach et al., 2003). The aim of the current study was to explore the influence of SB on inspiratory and expiratory muscle fatigue (IMF and EMF, respectively) during front crawl (F/C) swimming. METHODS: Following institutional ethical clearance, 6 competitive University swimmers were recruited (mean ± SD: age 20 ± 1.0 years; body mass 74.6 ± 8.6 kg; stature 175.2 ± 10.5 cm) to undertake 3 x 200m F/C swims of different breathing conditions in a swimming flume: 1x: ad libitum (ALB), controlled frequency breathing (CFB) and SB. The order of the swims was randomised, and following a standardised 500m warm-up, were completed at a swimming velocity equivalent to 90% of each swimmer`s season best time. Inspiratory and expiratory mouth pressure (MIP and MEP, respectively, RPM, Micro Medial, UK) were recorded pre and post each 200m swim. RESULTS: Two way repeated measures ANOVA revealed no significant differences in MIP between conditions (p = 0.265), although baseline MIP (149 ± 36 cmH2O for ALB, 153 ± 30 cmH2O for CFB and 160 ± 32 cmH2O for SB) was significantly higher (p = 0.014) than post swim MIP (124 ± 33 cmH2O for ALB, 126 ± 39 cmH2O for CFB and 138 ± 27 cmH2O for SB). Similarly, baseline MEP (173 ± 50 cmH2O for ALB, 157 ± 38 cm- H2O for CFB and 177 ± 33 cmH2O for SB) was significantly higher (p = 0.045) than post swim MEP (150 ± 49 cmH2O for ALB, 146 ± 37 cmH2O for CFB and 163 ± 40 cmH2O for SB) but not different between conditions (p = 0.294). DISCUSSION: IMF and EMF both occur in response to sub-maximal 200m F/C swimming, but the magnitude of IMF and EMF is similar between SB, ALB and CFB in trained University swimmers. Whether SB creates a respiratory muscle training stimulus remains to be seen.